Cellular mechanisms of microplastic and nanoparticle exposure and its relationship with metabolic diseases: Literature review - Syarifah, Ismi Farah; Hasby, Rizal Maulana; Taupiqurrohman, Opik; Mahroji, Mokhamad (Biological Environment and Pollution, 2025)
Microplastics (MP) and nanoparticles (PS-NPs) are emerging environmental contaminants of significant concern due to their adverse effects on human health. This study systematically reviews the impact of these pollutants on cellular mechanisms, with a specific focus on their association with metabolic diseases. Data were collected from various scientific publications relevant to the research topic. Research findings indicate that exposure to microplastics (MP) can result in a reduction in triglyceride and total cholesterol levels, while also disrupting insulin signaling pathways, thereby contributing to insulin resistance. Additional studies have demonstrated that exposure to nanoparticles (PS-NPs) in pregnant mice may increase the risk of metabolic disorders in their offspring. Moreover, PS-NP exposure has been shown to exacerbate type 2 diabetes by inhibiting the AKT/GSK3β pathway. Collectively, exposure to microplastics and nanoparticles has the potential to aggravate metabolic disorders and increase the risk of metabolic diseases, including diabetes, obesity, and cardiovascular conditions. These findings offer valuable insights into the potential health risks associated with environmental exposure to microplastics and nanoparticles and underscore the critical importance of addressing microplastic pollution to human health.